Manajemen Pelayanan Haji dalam Peningkatan Kepuasan Jamaah Haji di Kantor Kementerian Agama Kabupaten Malang - Ula Masrurotuz Zahro; Samsul Susilawati; Muh Hambali (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the management of hajj services and its role in improving the satisfaction of hajj pilgrims at the Office of the Ministry of Religious Affairs of Malang Regency, which aims to evaluate the management of hajj services and the satisfaction of hajj pilgrims at the Office of the Ministry of Religious Affairs of Malang Regency. The type of research used is qualitative research with a phenomenological approach. Through this approach, which is intended to explain the existing conditions and problems in the environment of the Office of the Ministry of Religious Affairs of Malang Regency, this study evaluates current service management practices and identifies the main factors that contribute to the satisfaction of hajj pilgrims. The subjects of this study were hajj pilgrims who had performed the hajj and received services from the Office of the Ministry of Religious Affairs of Malang Regency. Data were collected using surveys, interviews, and observational studies involving hajj pilgrims and office staff. The findings of the study revealed that effective service management significantly improves various aspects of the hajj experience, especially in areas such as transportation logistics, accommodation quality, and administrative efficiency. This study underscores the need for continuous assessment of service management strategies to align with the evolving needs and expectations of pilgrims. By emphasizing a collaborative approach to service delivery, the study highlights the importance of better resource allocation, proactive problem solving, and integration of advanced technologies to improve service efficiency. The study’s insights provide valuable recommendations for policymakers and practitioners seeking to improve Hajj service standards and, as a result, overall pilgrim satisfaction. This study contributes to a deeper understanding of how optimized service management can transform the Hajj experience. By addressing key areas for improvement and adopting a responsive and pilgrim-centered approach, the Ministry of Religious Affairs Office in Malang Regency can ensure a more fulfilling and spiritually satisfying Hajj journey for pilgrims. The implications of this study extend beyond the local context, offering valuable lessons for Hajj service providers globally in their efforts to improve pilgrim satisfaction and service quality.